Analysis of autophagic flux in response to sulforaphane in metastatic prostate cancer cells. Issue 10 (13th August 2015) - Watson, Gregory W.; Wickramasekara, Samanthi; Fang, Yufeng; Palomera‐Sanchez, Zoraya; Maier, Claudia S.; Williams, David E.; Dashwood, Roderick H.; Perez, Viviana I.; Ho, Emily
<x xml:space="preserve">Abstract</x> Scope The phytochemical sulforaphane (SF) has been shown to decrease prostate cancer metastases in a genetic mouse model of prostate carcinogenesis, though the mechanism of action is not fully known. SF has been reported to stimulate autophagy, and modulation of autophagy has been proposed to influence SF cytotoxicity; however, no conclusions about autophagy can be drawn without assessing autophagic flux, which has not been characterized in prostate cancer cells following SF treatment. Methods and results We conducted an investigation to assess the impact of SF on autophagic flux in two metastatic prostate cancer cell lines at a concentration shown to decrease metastasis in vivo. Autophagic flux was assessed by multiple autophagy related proteins and substrates. We found that SF can stimulate autophagic flux and cell death only at high concentrations, above what has been observed in vivo. Conclusion These results suggest that SF does not directly stimulate autophagy or cell death in metastatic prostate cancer cells under physiologically relevant conditions, but instead supports the involvement of in vivo factors as important effectors of SF‐mediated prostate cancer suppression.